2020
DOI: 10.1007/s11325-020-02203-0
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Risk of COVID-19 Infection, Hospitalization and Respiratory Failure

Abstract: Purpose To study the relationship between OSA and risk of COVID-19 infection and disease severity, identified by the need for hospitalization and progression to respiratory failure. Methods We queried the electronic medical record system for an integrated health system of 10 hospitals in the Chicago metropolitan area to identify cases of COVID-19. Comorbidities and outcomes were ascertained by ICD-10-CM coding and medical record data. We evaluated the risk for COVID-19 diagnosis, hospitalization, and respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 10 publications
7
138
0
5
Order By: Relevance
“…Maas et al conducted a retrospective study to estimate the risk for coronavirus disease 2019 (COVID-19) infection in patients with obstructive sleep apnea (OSA) and to study the relationship between OSA and COVID-19 disease severity [1]. The researchers concluded that patients with OSA experienced an 8fold greater risk for COVID-19 in comparison to a control group derived from a large patient registry including data from 10 different hospitals.…”
Section: Dear Editormentioning
confidence: 99%
“…Maas et al conducted a retrospective study to estimate the risk for coronavirus disease 2019 (COVID-19) infection in patients with obstructive sleep apnea (OSA) and to study the relationship between OSA and COVID-19 disease severity [1]. The researchers concluded that patients with OSA experienced an 8fold greater risk for COVID-19 in comparison to a control group derived from a large patient registry including data from 10 different hospitals.…”
Section: Dear Editormentioning
confidence: 99%
“…Unfortunately, until now, the evidence regarding the link between OSA and COVID-19 is still conflicting. Several observational studies showed that the presence of OSA was associated with poor COVID-19 outcomes [ 15 , 16 , 17 ] , but several others showed that OSA did not alter the outcomes of COVID-19 18 , 19 . This article aims to explore and give clear evidence regarding the potential association between OSA and poor outcomes of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep plays an importnat role in regulation of cellular as well as humoral immunity and sleep deprivation can reduce immune response [ 10 ]. Subjects with obstructive sleep apnea have been found to have an increased risk of contracting SARS-CoV-2 infection, getting hospitalized, and developing respiratory failure [ 14 ]. Thus, an adequate amount of optimal quality sleep appears an important factor to counteract infection.…”
mentioning
confidence: 99%
“…At a larger level, sleep medicine services have been impacted globally during the COVID-19 pandemic [ 14 – 16 ]. Considering the important association between sleep and SARS-CoV-2 infection, several societies have proposed guidelines to mitigate sleep disorders and using telemedicine facilities to manage patients during the pandemic.…”
mentioning
confidence: 99%